Relación entre el valor de la proteina C reactiva y los hallazgos quirúrgicos de apendicitis aguda en los pacientes atendidos en el servicio de cirugía HRIA. - Gallardo Yaguana, Diana Estefanía (2016)
This study is a work that guides us on the relationship between surgical findings of patients diagnosed with acute appendicitis and C-reactive protein values. This is a cross-sectional descriptive study, where 54 cases of patients who were diagnosed with acute appendicitis were analyzed and who they underwent surgery in the period between the months February- July 2015 in the service of General Surgery Hospital Isidro Ayora of Loja city. The objectives were to identify the value of the PCR, describe the surgical findings of acute appendicitis and define the relationship between these two variables. .In this way surgical findings with surgical pre CRP correlated, finding a close relationship between the stage or severity of the disease and increase the value of c-reactive protein. The results of the research shows that 44.4% of patients had acute appendicitis phase II with C-reactive protein values between 2 to 10.99 mg / dl, while appendicitis grade III and IV represent 22.2 and 29.6% respectively with PCR values ranging from 11 mg / dl on. Therefore, in this study we can conclude that CRP serves as a contributing factor in determining the degree of appendicitis and could be considered as part of the protocol care for patients with suggestive symptoms of acute appendicitis.